2012
DOI: 10.1080/02786826.2012.701784
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Gradients and Chemical Characterization of Particulate Matter from Vehicular Traffic near Major Roadways: Results from the 2009 Queens College Air Quality Study in NYC

Abstract: We present measurements of traffic-related pollutants made near the Long Island Expressway (LIE, I-495), in Queens, NewYork. The Aerodyne Research Inc. (ARI) mobile laboratory (AML) was deployed to map spatial and temporal gradients of gas-phase species and particulate matter (PM) associated with vehicular exhaust in the residential areas near the LIE. We observe that pollutant levels build up during the early morning hours under stable boundary layer conditions yet fall off quickly within 150 m downwind of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 104 publications
22
109
0
Order By: Relevance
“…The average ratio drops to about 1.05 if the three major oxygenated organic fragments, including CO + , CO + 2 , and C 2 H 3 O + , are also excluded in the calculation. Using the same measurement approach and R BC -dependent CE, Massoli et al (2012Massoli et al ( , 2015 reported that 81 and 87 % of HOA was associated with rBC particles near vehicular emissions and in a polluted offshore environment.…”
Section: Comparisons Of Nr-pm Rbc and Nr-pm Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average ratio drops to about 1.05 if the three major oxygenated organic fragments, including CO + , CO + 2 , and C 2 H 3 O + , are also excluded in the calculation. Using the same measurement approach and R BC -dependent CE, Massoli et al (2012Massoli et al ( , 2015 reported that 81 and 87 % of HOA was associated with rBC particles near vehicular emissions and in a polluted offshore environment.…”
Section: Comparisons Of Nr-pm Rbc and Nr-pm Componentsmentioning
confidence: 99%
“…Real-time and mass-based chemical compositions of organic coatings on ambient BC particles were seldom reported until the recent development of an Aerodyne soot-particle aerosol mass spectrometer (SP-AMS; Cappa et al, 2012;Massoli et al, 2012Massoli et al, , 2015Onasch et al, 2012;Liu et al, 2015;Lee et al, 2016;Willis et al, 2016). In this study, we investigate formation of organic coatings on BC particles by deploying a SP-AMS in Fontana, California, which is located in the broader South Coast Air Basin and includes the greater Los Angeles area.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize this spatial variation, dense networks of stationary monitors can be deployed, but mobile monitoring is often preferred because of the increased spatial flexibility (Baldauf et al, 2008;Choi et al, 2012;Durant et al, 2010;Hagler et al, 2012;Kozawa et al, 2009;Zwack et al, 2011a;Rooney et al, 2012;Westerdahl et al, 2005;Drewnick et al, 2012;Massoli et al, 2012). Broader surveys of ambient air quality are also frequently conducted using mobile monitoring on a scale ranging from neighborhood to country in order to characterize regional concentrations or locate previously unknown hotspots (Hagler et al, , 2010Arku et al, 2008;Adams et al, 2012;Farrell et al, 2013;Drewnick et al, 2012;Van Poppel et al, 2013;Hu et al, 2012).…”
Section: Recreational Vehiclementioning
confidence: 99%
“…The general operation of the AMS (Jayne et al 2000;Drewnick et al 2005;Canagaratna et al 2007) and AMS particle focusing (Liu et al 1995;Liu et al 2007) have been described previously in the literature and used for a wide range of emissions sources (Canagaratna et al 2004;Herndon et al 2005c;Lack et al 2009;Massoli et al 2012). Onasch et al (2009), Timko et al (2010b, 2011, 2013, and Yu et al (2010) have described the use of the AMS specifically to characterize aircraft exhaust PM.…”
Section: The Aerosol Mass Spectrometermentioning
confidence: 99%